2018
DOI: 10.1002/mds.27381
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility MRI captures nigral pathology in patients with parkinsonian syndromes

Abstract: Susceptibility MRI measurements capture nigral pathologies associated with parkinsonian syndromes. Whereas quantitative susceptibility mapping is more sensitive to iron, R2* may reflect pathological aspects of the disorders beyond iron such as α-synuclein. They may be invaluable tools in diagnosing differential parkinsonian syndromes, and tracking in living patients the dynamic changes associated with the pathological progression of these disorders. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…The fact that R2* changes in the SNc persisted even after adjusting for QSM suggests that R2* may capture, in addition to iron, the complex microstructural changes occurring during PD progression. Consistent with this, Lewis et al demonstrated that R2* also may reflect α‐synuclein and possibly neuronal cell loss in the SN.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The fact that R2* changes in the SNc persisted even after adjusting for QSM suggests that R2* may capture, in addition to iron, the complex microstructural changes occurring during PD progression. Consistent with this, Lewis et al demonstrated that R2* also may reflect α‐synuclein and possibly neuronal cell loss in the SN.…”
Section: Discussionmentioning
confidence: 67%
“…In recent years, both R2* and the newer quantitative susceptibility mapping (QSM) measures have been used to estimate iron content in brain tissue, with the latter reported to be more sensitive . Of the 2 sequences, Lewis et al confirms that in vivo QSM correlates better with iron content in postmortem brain tissue, whereas R2* may also capture other aspects of PD‐related pathology, such as α‐synuclein and possibly neuronal cell loss, in addition to tissue iron content. Several cross‐sectional studies have demonstrated higher R2* and QSM in the SN of PD patients and fueled enthusiasm for using these susceptibility MRI metrics to gauge PD progression.…”
mentioning
confidence: 99%
“…29 In a recent autopsy cohort of 14 subjects, we found non-movement disorder specialists can predict pathology in less than 50% of cases. 30 There is a clear need for an early detection marker in PD patients that has high accuracy and translational value. The current best marker is proposed by Nalls et al, 31 who used a combination of clinical and genetic information and found an AUC=0.926 for classifying PD patients from controls.…”
Section: Discussionmentioning
confidence: 99%
“…Lewis and colleagues provide a unique study to compare susceptibility measurements from a T2*‐weighted multigradient‐echo sequence and pathology from tissue in the same individuals. The authors compared R2* and quantitative susceptibility mapping (QSM) of the SN directly with pathology, including SN cell counts, α‐synuclein, tau, and iron quantification.…”
mentioning
confidence: 95%
“…Three types of biomarkers were investigated that can investigate iron load, neuromelanin content, and microstructural changes using diffusion imaging in the SN. The findings from these articles use different designs and cut across pathological validation and longitudinal progression of MRI iron‐sensitive markers in the SN, the relationship between neuromelanin changes in the SN and brain stem atrophy in PSP, and diffusion changes in a novel at‐risk cohort …”
mentioning
confidence: 99%